Contribuição para. o conhecimento da "saúva de vidro" Atta laevigata Fred. Smith, 1858 - Castro, Urbano de Paiva; Zamith, Adiel P. L.; Mariconi, Francisco A. M. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1961)
In 1961, field investigations on "saúva de vidro" (parasol ant, Atta laevigata (Fred. Smith, 1858) were carried out at Piracicaba and other regions of the State of São Paulo (Brazil). This species was found to be a serious pest of cultivated plants, specially Eucalyptus and cotton. The ant makes its colony in any kind of soil, but it prefers to live in the poor ones.